Upaya Arbitrase dalam Penyelesaian Perselisihan Hubungan Industrial Didasarkan Adanya Kesepakatan Para Pihak - Andika Dwi Yuliardi; Imam Budi Santoso (Faculty of Law Hang Tuah University, 2022)
One of the efforts to settle out of court is arbitration by emphasizing the principle of a win-win solution. The purpose of this paper is to find out the procedure for resolving industrial relations disputes through arbitration, and to find out the factors that cause arbitration to be less attractive. The type of research used is normative juridical research with a statutory approach. The results of the study indicate that the Arbitrator is obliged to settle industrial relations disputes within a maximum of 30 days, which can be extended to a maximum of 14 working days upon the agreement of the parties. Prior to that, peace is sought, if that fails, the arbitration trial will continue. One or the parties may apply for the cancellation of the arbitration award to the Supreme Court within a period of 30 days from the stipulation of the arbitrator's decision. Factors causing arbitration to be less desirable, namely Industrial Relations Arbitration does not have the authority to settle disputes over rights, settlement through arbitration is not yet familiar enough, arbitration can only be beneficial for honest and trustworthy parties, absolute dependence on arbitrators, there is no precedent for previous arbitration decisions, not possible to object.